2017
DOI: 10.1111/hae.13184
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two types of ankle supports in men with haemophilia and unilateral ankle pain from arthropathy

Abstract: This study suggests that pain relief from both types of braces is identical but use of a CF-AFO does not alter gait patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…In some cases of pes cavus, a metatarsal bar together with heel cushioning was used . On some occasions, the subject's degree of hindfoot deformity and/or ankle instability made it necessary to resort to some other kind of orthosis (UCLB‐University of California Berkeley Laboratory, PTB‐Patellar Tendon Bearing, Aircast) or to custom orthopaedic footwear …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In some cases of pes cavus, a metatarsal bar together with heel cushioning was used . On some occasions, the subject's degree of hindfoot deformity and/or ankle instability made it necessary to resort to some other kind of orthosis (UCLB‐University of California Berkeley Laboratory, PTB‐Patellar Tendon Bearing, Aircast) or to custom orthopaedic footwear …”
Section: Resultsmentioning
confidence: 99%
“…Kavlak et al compared custom orthoses to orthopaedic footwear and found significant evidence that custom orthoses relieve pain and reduce disability during the performance of activities of daily living (ADL). In the context of haemophilia, studies also suggest that insoles and orthopaedic shoes may also exert a beneficial effect on PWH ankle joints …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations